Impaired non-specific delayed cutaneous hypersensitivity in bird fancier's lung. Issue 2 (February 1989) - Orriols, R; Morell, F; Curull, V; Roman, A; Sampol, G
Abstract : The relation between non-specific delayed cutaneous hypersensitivity and bird fancier's lung was investigated in 13 patients with the disorder. They were compared with 50 subjects who had no reason to have decreased non-specific delayed cutaneous hypersensitivity (control group) and 34 patients with pulmonary sarcoidosis. In addition, 13 patients with bird fancier's lung (11 of the original group) were tested at least one year after avoiding exposure to the causal antigen. Five antigens (candidine, staphylococcal toxoid, tuberculin purified protein derivative, trichophyton, and streptokinase-streptodornase) were injected intradermally (0.1 ml) and the mean weal diameter was measured at 48 hours. The mean weal size was significantly less in the subjects with bird fancier's lung at the time of diagnosis than in the control group (2.23 v 5.66 mm) but did not differ significantly from that of the subjects with sarcoidosis (2.80 mm) or from that of the bird fanciers with no exposure to the causal antigen for one year (2.75 mm). The impairment of non-specific delayed cutaneous hypersensitivity in patients with bird fancier's lung appears to be quantitatively similar to that occurring in sarcoidosis.